2000
DOI: 10.1002/1096-8652(200011)65:3<204::aid-ajh5>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of ?-interferon or dexamethasone as maintenance treatment for multiple myeloma

Abstract: In order to assess the role of alpha-interferon or dexamethasone as maintenance therapy for multiple myeloma, 172 consecutive, previously untreated patients with disease of low or intermediate tumor mass received primary therapy with oral melphalan and intermittent, high-dose dexamethasone (MD), repeated monthly. Within 5 months, 84 responding patients were assigned at random to maintenance treatment with alpha-interferon (3 mU s.c. 3 x weekly) or dexamethasone (20 mg/m2 p.o. each morning for 4 days) repeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 28 publications
0
23
0
1
Order By: Relevance
“…19,20 Since maintenance interferon does not improve outcome, this benefit may be observed with the use of glucocorticoids alone. Although pulse dexamethasone produced a similar outcome to 3-times-a-week interferon maintenance therapy among patients responding to MD induction therapy, 21 the type and length of induction therapy (melphalan-containing compared with VAD-like regimens) and the type, dose, and schedule of steroids may be critical to their efficacy during maintenance therapy. In fact, patients received only a median of 2.5 months (maximum, 4.9 months) of induction MD therapy, 21 and this short induction period is unlikely to be long enough to produce a maximal antimyeloma effect with the use of a melphalan-based regimen.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…19,20 Since maintenance interferon does not improve outcome, this benefit may be observed with the use of glucocorticoids alone. Although pulse dexamethasone produced a similar outcome to 3-times-a-week interferon maintenance therapy among patients responding to MD induction therapy, 21 the type and length of induction therapy (melphalan-containing compared with VAD-like regimens) and the type, dose, and schedule of steroids may be critical to their efficacy during maintenance therapy. In fact, patients received only a median of 2.5 months (maximum, 4.9 months) of induction MD therapy, 21 and this short induction period is unlikely to be long enough to produce a maximal antimyeloma effect with the use of a melphalan-based regimen.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, the MD Anderson group (Houston, TX) randomized 84 patients responding to intermittent oral melphalan and high-dose oral dexamethasone (MD) to maintenance treatment with either ␣-interferon (3 mIU subcutaneously 3 times weekly) or pulse oral dexamethasone (20 mg/m 2 for 4 days monthly) until relapse. 21 Importantly, among patients randomized to maintenance treatment, the duration of induction therapy was limited to a median of only 2.5 months. Although there was no difference in duration of response or overall survival between the 2 maintenance treatments, the authors showed that more patients responded to resumption of MD treatment following relapses from interferon (82%) compared with dexamethasone (44%) maintenance treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Alexanian et al did randomize patients treated initially with melphalan and intermittent, high-dose dexamethasone to receive maintenance with either α-interferon or dexamethasone. 51 Both regimens resulted in similar median remission durations of 10 months, though patients who received interferon had a higher likelihood of responding to MD if this was reinstituted at the time of relapse, suggesting a possible benefit for interferon. However, when interferon-α-2b was studied as a maintenance regimen in a randomized fashion compared with observation alone in patients initially treated with MP, a benefit was not seen.…”
Section: Maintenance Therapymentioning
confidence: 98%
“…Complete response rate has historically correlated poorly with overall survival (Baldini 1991;Riccardi et al, 2003;Durie et al, 2004), and clearly does not take account of quality of life aspects, which are affected by increasingly prolonged myeloma therapy regimens. In early trials, time to progression did correlate with overall survival, but with consolidation treatment this association is no longer seen (Alexanian et al, 2000;Attal et al, 2012;Maiolino et al, 2012;Sonneveld et al, 2012;Stewart et al, 2013). PFS2, the time from first treatment to second relapse, takes account of tumour resistance induced by the first line of treatment, and to date studies have shown it is prolonged in association with PFS (Palumbo et al, 2014b;Tacchetti et al, 2014), but it has not yet been validated as a surrogate for OS, and still takes years of follow up to report mature data.…”
Section: Trial Endpointsmentioning
confidence: 95%
“…A therapeutic dose of prednisolone conferred a survival benefit when used after VAD-based conventional chemotherapy (Berenson et al, 2002) but glucocorticoids as monotherapy in the post-ASCT population are redundant now given the improved clinical activity and tolerability observed with IMiDs and proteasome inhibitors. In a phase III comparison between dexamethasone and interferon maintenance, the dexamethasone group responded very badly to melphalan/dexamethasone at relapse, presumably due to selection of resistant clones (Alexanian et al, 2000).…”
Section: Maintenancementioning
confidence: 99%